Information Encryption in Ghost Imaging With Customized Data Container and XOR Operation - Yi Qin; Yingying Zhang (IEEE Photonics Journal)
The conventional ghost-imaging-based encryption (GIE) scheme has low-quality decrypted images and unsatisfied security. In this paper, we propose to cope with these issues using customized data container and exclusive-OR (XOR) operation. The proposal constitutes two security levels. The first level includes transforming the primary information into a binary signal (i.e., bit stream) under the ASCII standard and XORing it with the key bit stream. In the second step, the result in the first level is codified into an elaborate data container, which is then sent to the GIE scheme. The proposed approach not only possesses high security but ensures lossless recovery of the primary information as well. Its validity and feasibility have been supported by a series of numerical results.